Devonian upper ocean redox trends across Laurussia: Testing potential influences of marine carbonate lithology on bulk rock I/Ca signals - He, Ruliang; Elrick, Maya; Day, James; Lu, Wanyi; Lu, Zunli (Frontiers in Marine Science, 2022)
The Devonian is characterized by major changes in ocean-atmosphere O2 concentrations, colonialization of continents by plants and animals, and widespread marine anoxic events associated with rapid δ13C excursions and biotic crises (e.g., Becker et al., 2012). However, the long-term upper ocean redox trend for the Devonian is still not well understood. This study presents new I/Ca data from well-dated Lower Devonian through Upper Devonian limestone sections from the Great Basin (western Laurussia) and the Illinois Basin (central Laurussia). In addition, to better address potential influences of lithology and stratigraphy on I/Ca redox signals, I/Ca data are reported here as carbonate lithology-specific. Results indicate that lithologic changes do not exert a dominant control on bulk carbonate I/Ca trends, but the effects of some diagenetic overprints cannot be ruled out. For the Illinois Basin, low I/Ca values (more reducing) are recorded during the Pragian to Emsian and increased but fluctuating values are recorded during the Eifelian to Givetian. The Great Basin I/Ca trends suggest local upper oceans were more reducing in the Lochkovian, more oxic in the Pragian-Emsian, return to more reducing in the Eifelian, then to increasingly more oxic, but fluctuating in the Givetian-Frasnian. The local I/Ca variations at Great Basin likely share more similarity with global upper ocean condition (compared to the Illinois Basin) based on its position adjacent to the Panthalassic Ocean and its temporal co-variation with global environmental volatility trends. The overall reducing and variable redox conditions of local upper ocean (if not a diagenetic signal) during the Middle and Late Devonian of Great Basin coincide with evidence of increased global environmental volatility suggesting seawater redox may have been an important part of environmental instability at this time.